Pro ASP.NET 4 CMS Advanced Techniques for C# Developers Using the .NET 4 Framework - Harris, Alan.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
To be a successful ASP.NET 4 developer, you need to know how to apply the vast array of new functionality available in the latest release of the .NET 4 Framework and Visual Studio 2010. This book will immerse you in a variety of advanced topics, including architecting different application data tiers, memory caching paradigms, data mining, and search engine optimization. Working through step-by-step exercises using P/LINQ, DLR, MEF, MVC, IronPython, Axum, and Ajax, you will learn a variety of approaches to building each of the key application tiers common to all web solutions. Using a proven technique of illustrating advanced concepts with functional solutions, all topics in the book are modeled on a fully operational content management system (CMS), built from the ground up. This ensures that you$1 (Bll be introduced to real-world examples that demonstrate the full functionality of the .NET 4 Framework for ASP.NET, and that you$1 (Bll be able to apply your new skills to any web development situation.s
Keywords: Computer science; Computer Science; Programming Techniques